Fatty acids secreted from head and neck cancer induce M2-like Macrophages. Issue 4 (25th February 2022) - Albakri, Marwah M; Huang, Stanley Ching-Cheng; Tashkandi, Hammad N; Sieg, Scott F
Abstract: Tumor-infiltrating monocytes can mature into Macrophages that support tumor survival or that display antitumor properties. To explore mechanisms steering Macrophage maturation, we assessed the effects of supernatants from squamous cell carcinoma cell lines (FaDu and SCC) on monocyte-derived Macrophage maturation. Purified monocytes were incubated in medium or medium supplemented with supernatants from FaDu and SCC9 or the leukemia monocytic cell line, THP-1. Macrophages were examined for markers of maturation (CD14, CD68), activation (HLA-DR, CD86, IL15R), scavenger receptor (CD36), toll-like receptor (TLR4), M2 marker (CD206), immune checkpoint (PD-L1), and intracellular chemokine expression (IP-10). Compared to other conditions, cells incubated with FaDu or SCC9 supernatants displayed enhanced survival, down-regulation of cell surface HLA-DR, CD86, IL-15R, CD36, and intracellular IP-10 expression, and increased cell surface PD-L1, CD14, and CD206 expression. Despite expressing TLR4 and CD14, Macrophages matured in tumor supernatants failed to respond to stimulation with the canonical TLR4 agonist, LPS. These changes were accompanied by a decrease in intracellular phospho-p38 expression in tumor supernatant conditioned Macrophages. Depletion of fatty acids from tumor supernatants or treatment of cell cultures with an inhibitor of fatty acid oxidation, Etomoxir, reversed a number of these phenotypic changes induced by tumor supernatants. Additionally, Macrophages incubated with either palmitic acid or oleic acid developed similar phenotypes as cells incubated in tumor supernatants. Together, these data suggest that fatty acids derived from tumor cells can mediate the maturation of Macrophages into a cell type with limited pro-inflammatory characteristics. Graphical Abstract: Fatty Acids from head and neck tumor cell lines mediate maturation of macrophages into cells with a limited pro-inflammatory phenotype.